More recent insights into the breast cancer burden across BRICS-Plus: Health consequences in key nations with emerging economies using the global burden of disease study 2019 - Mubarik, Sumaira; Luo, Lisha; Iqbal, Mujahid; Nawsherwan,; Bai, Jianjun; Yu, Chuanhua (Frontiers in Oncology, 2023)
Brazil, Russia, India, China, South Africa, and 30 other Asian nations make up the BRICS-Plus, a group of developing countries that account for about half of the world's population and contribute significantly to the global illness burden. Objectives: This study aimed to analyzed the epidemiological burden of female breast cancer (BC) across the BRICS-Plus from 1990 to 2019 and studied the associations with age, period, birth cohort and countries' sociodemographic index (SDI). In 2019, there were about 1.98 million female BC cases (age-standardized rate of 45.86 [95% UI: 41.91, 49.76]) and 0.69 million deaths (age-standardized rate of 15.88 [95% UI: 14.66, 17.07]) around the globe. Among them, 45.4% of incident cases and 51.3% of deaths were attributed to the BRICS-Plus. China (41.1% cases and 26.5% deaths) and India (16.1% cases and 23.1% deaths) had the largest proportion of incident cases and deaths among the BRICS-Plus nations in 2019. Pakistan came in third with 5.6% cases and 8.8% deaths. Over the past three decades, from 1990 to 2019, the BRICS-Plus region's greatest AROC was seen in Lesotho (2.61%; 95%UI: 1.99-2.99). The birth cohort impacts on BC vary significantly among the BRICS-Plus nations. Overall, the risk of case-fatality rate tended to decline in all BRICS-Plus nations, notably in SAARC and China-ASEAN FTA nations, and the drop in risk in the most recent cohort was lowest in China and the Maldives. Additionally, there was a substantial negative link between SDI and case fatality rate (r1990= -0.91, p<0.001; r2019= -0.89, p<0.001) in the BRICS-Plus in both 1990 and 2019, with the EEU nations having the highest case fatality rate. The BC burden varies remarkably between different BRICS-Plus regions. Although the BRICS’ efforts to regulate BC succeeded, the overall improvements lagged behind those in high-income Asia-Pacific nations. Every BRICS-Plus country should strengthen specific public health approaches and policies directed at different priority groups, according to BRIC-Plus and other high-burden nations.